Bridging the gap: How technology facilitates conceptual understanding in mathematics - Fauzi, Azra; Hardyanti, Hardyanti; Suryaningsih, Sri (Universitas Islam Negeri Raden Intan Lampung, 2026)
The integration of technological tools into mathematics instruction has increased rapidly in secondary schools, but their effectiveness in improving students’ conceptual understanding remains unclear. This mixed-methods study aimed to investigate how technological tools influence students’ conceptual understanding in mathematics and to explore students’ and teachers’ perceptions of technology-based learning in secondary schools. Data were collected through surveys, semi-structured interviews, and classroom observations. Findings revealed a critical gap: although technology significantly increased engagement (65–85%), only 30% reported improved conceptual understanding. Five themes emerged: visualization support, blended learning preferences, resource limitations, teacher training needs, and demand for interactivity. The study concluded that technology enhances mathematics learning when integrated with adequate resources and teacher training and provided evidence-based recommendations for technology integration strategies that balance digital innovation with traditional pedagogy. The study implied that technology can effectively support mathematics learning when integrated with adequate infrastructure, interactive learning designs, and sufficient teacher training.